Analysis of the Mathematical Comprehension Ability of Grade VIII Students on the Pythagorean Theorem - Rheta Puspita Sari (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2023)
This study aims to describe students' mathematical understanding abilities, especially in circle material. This research was conducted at MTs Nurul Yaqin Pekanbaru to 10 grade VIII students. The method used in this study is a descriptive method using a qualitative approach to analyze student answers from the given instrument. The instrument used in this study was a written test of mathematical comprehension ability with two questions. Based on the results of data analysis, it can be seen that the mathematical understanding ability of class VIII students at MTs Nurul Yaqin Pekanbaru is still relatively low. Students cannot apply formulas in simple calculations, perform algorithmic calculations, and do not understand the questions given. During learning, only a few students actively asked and answered questions given by the teacher. Students who were less active in the learning process tended to listen and take notes delivered by the teacher. Students had difficulty understanding questions, were not challenged to solve non-routine math problems, were nervous about answering questions about poorly understood mathematic material, were doubtful about being able to learn difficult mathematic material on their own, and were unable to find new ways to do difficult math problems.